Tagalog slang dictionary - Zorc, R. David; San Miguel, Rachel; Sarra, Annabelle M.; Afable, Patricia O. (Manila, Philippines De La Salle University Press, 1993)
Recordings of such neologism (new word or meaning) that were counter-checked with the standard Tagalog-English dictionary to cull out "gay language". It provides definitions for words that cannot be found in already existing resources. Includes curses and sexually explicit terms.
First published by Dunwood Press, 1991, Kensington, MD, U.S.A.
Includes bibliographical references (page xx)
Keywords: Tagalog language -- Dictionaries -- English; Tagalog language -- Slang -- Dictionaries